The Importance Of Company Age As A Moderation To Solve Financial Distress Problems: Case Study Of The Manufacturing Industry In Indonesia - Santi Octaviani (Brilliant International Journal Of Management And Tourism, 2023)
Study This aim For test influence operating capacity and leverage against financial distress with age company as moderating variable in Registered Manufacturing Companies on the Indonesian Stock Exchange for the 2018-2022 period. Research methods This is method quantitative. Population in study This is company manufacturers listed on the Indonesian Stock Exchange for the 2018-2022 period. Research methods sample done with use purposive sampling method, based on criteria that have been determined there were 132 companies used as sample. The analytical method used is method analysis multiple linear regression and processed use tool help SPSS Version 25. Test result show that: (1) Operating Capacity influential to Financial Distress, (2) Leverage influential significant to Financial Distress, (3) Company Age No moderate influence Operating Capacity to Financial Distress, (4) Company Age moderates strengthen influence Leverage to Financial Distress.